Pengembangan Media Pembelajaran Interaktif Melalui Smart Apps Creator Berbasis Android pada Mata Pelajaran IPA - Salakhuddin Ghani; Maslikhah Maslikhah (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2023)
The purpose of this research is to: (1) Analyze the need for interactive learning media development through Android-based Smart Apps Creator to improve cognitive learning outcomes in Class V students at MI NU Sabilul Ma'arif Islamiyah District Gebog Kudus Regency; (2) Develop interactive learning media through Android-based Smart Apps Creator with minimum validity in the good/worthy category (3) Test the effectiveness of interactive learning media development through Android-based Smart Apps Creator to improve cognitive learning outcomes in Class V students at MI NU Sabilul Ma'arif Islamiyah District Gebog Kudus Regency. The method used is the research and development method or Reseacrh and Development. The research and development steps in this study use the Borg & Gall development model which has been modified from 10 stages to 8 stages to be more efficient in terms of time and cost. Data collection techniques for data collection in this development research using interview guidelines, scales (questionnaires) and tests Data analysis techniques were analyzed using qualitative and quantitative analysis techniques. The results of this study indicate that: (1) The need for interactive learning media development through Android-based Smart Apps Creator to improve students' cognitive learning outcomes consisting of text display, image display, audio use, media function on android and media benefits in science learning with material coverage, material accuracy aspects and interactive learning aspects, (2) The development of interactive learning media through smart apps creator based is carried out through several stages including the design stage, validation, revision, small group trials and large group trials. (3) The development of interactive learning media through Android-based smart apps creator effectively improves students' cognitive learning outcomes. It is evident from the results of the analysis that shows an increase in the average student cognitive learning outcomes through the difference in average scores (t test) of 0.00, = 0,00< 0,05 so that it can be said that there is a difference in student cognitive learning outcomes in the pretest and posttest.